Dynamic sensitivity‐based clustering of distributed energy resources using LoRaWAN technology for voltage regulation in distribution networks - Ameen Gargoom; Mohammed Elmusrati; Ahmed Gaouda (IET Generation, Transmission & Distribution)
Abstract As the penetration level of renewable energies increases, many inverter‐based resources (IBRs) managing algorithms are proposed to control the impact of this penetration on the system. Some of these algorithms are based on a local control without visualizing the status of the whole network and others are based on a centralized control approach that results in dynamic settings without considering the mutual sensitivity among different IBRs. Hence, flexible management of IBRs to be simultaneously controlled either locally or remotely and satisfy technical and fair utilization at IBRs and systems levels becomes essential. The proposed flexible management algorithm suggested a dynamic setting that estimates the mutual sensitivity among IBRs at the system level and assures fairness among different owners. This mutual sensitivity link provides a quantifying measure of IBRs injected power on the status of the whole network. Furthermore, this measure defines dynamic clusters' boundaries that are continuously updated by including the most sensitive IBRs and updating their dynamic settings. This update takes place as system configuration, loads, and available sun‐power change in order to satisfy the flexible management algorithm without impacting fairness. The algorithm is applied on a sample DN and imposes compliance with system standard limits within a time‐frame of the stand‐alone LoRaWAN communication platform.